The Political economy of global restructuring - Rima, Ingrid Hahne, 1925- (New dimensions in political economy, 1993)
The Political Economy of Global Restructuring argues that the study of political economy, and the classical perspective it offers, will become increasingly relevant as we approach the 21st century.